No Idle Threat: Exploring Threats and Violence in Persons with Mental Illness. Issue 4 (2nd October 2019) - Mitchell, Melanie; Palk, Gavan; Kavanagh, David
Abstract: Violent threats are common and, in the majority of cases, innocuous expressions of emotion. However, some threats result in violence and mental illness is a predictor for threat-related violence (TRV). This study aimed to explore threats and the precursors to TRV. A sample of 236 Australian threateners in the civil psychiatric system was obtained from incident reports. Violence risk factors, threat content and rates of TRV were explored via univariate analysis and logistic regression. Fifty-five percent of the threats resulted in violence with 64% of violence occurring within 24 hours of the threat. Threateners who were violence had higher rates of intellectual disability and active symptoms post-threat. Previous violence did not differentiate threateners who engaged in TRV. Regression analysis revealed that intellectual impairment, age, mental disorder symptoms, treatment adherence, and no substance use accounted for 46% of variance in TRV. While this research has limitations, it highlights that threats can serve as a warning of future violence in some cases and identifies potential indicators for threat assessment.